Evaluación volumétrica de especies forestales maderables y su contribución al ambiente en el centro de producción e investigación Pabloyacu - Pérez Bravo, José Luis (2012)
This research work is to determine the titration of forest timber species and its contribution to the environment in 02 hectares of Pabloyacusecondary forest production and research, using the Index of ecological value (IVI) and will serve as biometric have knowledge of the species found, the field evaluations were conducted during the months of October 2012 to March 2013, where it began with the cleanliness and the delimitation of the blocks. Taking as objectives: general biometric assess the volume of timber species and its contribution to the environment in 02 hectares of secondary forest and specific: To characterize the species forest timber in 02 hectares of area. It has dasometric inventory to determine the volume. Detennine the volume of each species per hectare and by radial class. The results obtained according to the raised aims were: One found 582 individuals and 37 forest species, being the species with major quantity of individuals the "Quinilla" Manilkarabidentata, followed of the "Tulloquiro", "Rupiña" Myrsinepellucida, "Azarquiro" Pentagonia praises, "Shimbillo" Inga thibaudiana, "Knave Caspi " Mabea sp. The species with rnajor number of individuals is the Quinilla and Tulloquiro with 72 and 56 individuals respectively, later they are the Azarquiro, Shimbillo and Knave caspi with 35, 34, 32 individuals, then we have Stocking, HuanniHuanni, Caraña and Mullaca with 28, 27, 23 and 20 individuals respectively~ followed by the Moena, Sacha Shimbil1o and Iron Caspi with 17, 16 and 15 individuals respectively, later we have to the Onion Mocahua, Milk Caspi and QuilloSisa with 13 individuals and finally we ha ve the Ingaina with 1 O individuals being these spice her that they repeat themselves in all the blocks studied and studied. As for the biometric parameters we have to the species with rnajor basal area it is the Renaco, the species with rnajor total height is It was Wetting Caspi and the species with major total volume is the Shimbillo. Key words: forest species,ecological value